(untitled) (International Journal of Business, Economics and Management, 2022)
Urban rail transit is a widely applied mean of transportation in many cities around the world. In China, numerous cities are constructing their metro lines to improve the capability of its transportation and infrastructure. But because the investment needed in such project is colossal, the State Council in Beijing once criticized this type of investment for being wasteful and detaching from the actual demand of economic growth. Consequently, doubts on economic effects brought by metro system are also posed relentlessly. This research will try to look into the relation between the growing length of metro system and the economic growth in metropolis, finding out whether it is positive or negative and by what margin. And give out suggestions to city planners and policymakers on whether further construction of metro in mentioned cities should be carried out or approved. An econometric model that is based on the traditional Cobb-Douglas model and statistical methods including linear regression will be applied.